Pandemic Recovery: Persistent Disparities in Access to Elective Surgical Procedures. Issue 1 (3rd January 2023) - Lin, Joseph A.; Braun, Hillary J.; Schwab, Marisa E.; Pierce, Logan; Sosa, Julie A.; Wick, Elizabeth C.
Abstract : Objective: To examine potential disparities in patient access to elective procedures during the recovery phase of the COVID-19 pandemic. Summary of Background Data: Elective surgeries during the pandemic were limited acutely. Access to surgical care was restored in a recovery phase but backlogs and societal shifts are hypothesized to impact surgical access. Methods: Adults with electronic health record orders for procedures ("procedure requests"), from March 16 to August 25, 2019 and March 16 to August 25, 2020, were included. Logistic regression was performed for requested procedures that were not scheduled. Linear regression was performed for wait time from request to scheduled or completed procedure. Results: The number of patients with procedure requests decreased 20.8%, from 26, 789 in 2019 to 21, 162 in 2020. Patients aged 36–50 and >65 years, those speaking non-English languages, those with Medicare or no insurance, and those living >100 miles away had disproportionately larger decreases. Requested procedures had significantly increased adjusted odds ratios (aORs) of not being scheduled for patients with primary languages other than English, Spanish, or Cantonese [aOR 1.60, 95% confidence interval (CI) 1.12–2.28]; unpartnered marital status (aOR 1.21, 95% CI 1.07–1.37); uninsured or self-pay (aOR 2.03, 95% CI 1.53–2.70). Significantly longer wait times were seen for patients aged 36–65 years; with Medi-Cal insurance; from ZIP codes with lower incomes; and from ZIP codes >100 miles away. Conclusions: Patient access to elective surgeries decreased during the pandemic recovery phase with disparities based on patient age, language, marital status, insurance, socioeconomic status, and distance from care. Steps to address modifiable disparities have been taken.